SENTIMENT ANALYSIS OF THE HALODOC APPLICATION USING THE SUPPORT VECTOR MACHINE (SVM) ALGORITHM - Rachmadi Putri, Fairuz Amani; Siswanti, Sri (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The Halodoc application, as a digital healthcare service platform, has been widely used for various medical purposes, such as doctor consultations, medication purchases, and laboratory services. User interactions and reviews play a crucial role in enhancing service quality. Sentiment analysis was conducted using the Support Vector Machine (SVM) method to assess user perceptions and satisfaction based on reviews obtained from the Google Play Store platform. The analysis process included data collection, text preprocessing, data transformation using TF-IDF, and training an SVM model to predict sentiment. The model achieved its highest accuracy of 88.32% in the first scenario. However, accuracy slightly decreased in the second and third scenarios, reaching 86.25% and 86.94%, respectively. The analysis results indicated that the model performed best in the first scenario, with the lowest number of prediction errors. Additionally, the model was more accurate in classifying negative and positive sentiments than neutral ones.            Keywords: halodoc application; sentiment analysis; support vector machine algorithm Abstrak: Aplikasi Halodoc, sebagai platform layanan kesehatan digital, telah banyak digunakan untuk berbagai keperluan medis seperti konsultasi dokter, pembelian obat, dan layanan laboratorium. Interaksi pengguna dan ulasan mereka memiliki peran krusial dalam meningkatkan mutu layanan. Analisis sentimen dilakukan dengan menggunakan metode Support Vector Machine (SVM) untuk mengetahui persepsi dan kepuasan pengguna berdasarkan ulasan yang diperoleh dari Platform Google Play Store. Proses analisis mencakup pengumpulan data, pra-pemrosesan teks, transformasi data menggunakan TF-IDF, dan pelatihan model SVM untuk memprediksi sentimen. Hasil pelatihan model dengan akurasi tertinggi sebesar 88,32% pada skenario pertama. Akurasi sedikit menurun pada skenario kedua dan ketiga, masing-masing sebesar 86,25% dan 86,94%, Hasil analisa menunjukkan bahwa model memiliki performa terbaik pada skenario pertama dengan jumlah kesalahan prediksi terkecil. Selain itu, model cenderung lebih akurat dalam mengklasifikasikan sentimen negatif dan positif dibandingkan netral.. Kata kunci: algoritma support vector machine; analisis sentimen; aplikasi halodoc